2017
DOI: 10.5194/aab-60-27-2017
|View full text |Cite
|
Sign up to set email alerts
|

<i>SIRT1</i> gene polymorphisms associated with carcass traits in Luxi cattle

Abstract: Abstract. SIRT1 is the gene that codes for Sirtuin 1, an NAD (nicotinamide adenine dinucleotide)-dependent class III histone deacetylase. This gene plays a key role in adipose tissue and muscle development in animals. Chinese Luxi cattle (n = 169) were selected to identify SIRT1 SNPs (single nucleotide polymorphisms) and investigate the relationship of these SNPs with carcass traits. Five SNPs (g.-382G > A, g.-274C > G, g.17324T > C, g.17379A > G, and g.17491G > A) were identified by direct sequencing. SNPs g.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 27 publications
(21 reference statements)
1
9
0
Order By: Relevance
“…Milk quality was significantly affected only in terms of FC (3.84 % vs. 3.55 % for CC and GG cows, respectively; P < 0.05), with no difference in protein content. When production data during standard lactation are considered, no differences were found concern- Liu et al (2017) ing the quality of milk. Moreover, CG animals yielded a greater amount of milk when compared to cows belonging to CC genotype (5018.30 kg vs. 4165.67 kg; P < 0.05).…”
Section: Effects Of Polymorphism On Productive and Reproductive Traitsmentioning
confidence: 99%
See 4 more Smart Citations
“…Milk quality was significantly affected only in terms of FC (3.84 % vs. 3.55 % for CC and GG cows, respectively; P < 0.05), with no difference in protein content. When production data during standard lactation are considered, no differences were found concern- Liu et al (2017) ing the quality of milk. Moreover, CG animals yielded a greater amount of milk when compared to cows belonging to CC genotype (5018.30 kg vs. 4165.67 kg; P < 0.05).…”
Section: Effects Of Polymorphism On Productive and Reproductive Traitsmentioning
confidence: 99%
“…To date, only few studies have been conducted in order to find a possible relationship between SIRT1 gene polymorphisms and livestock performance traits. Nevertheless, the SIRT1 gene seems to be a potentially useful genetic marker for carcass and body measurement characteristics (Li et al, 2013a, b;Gui et al, 2014;Liu et al, 2017). In particular, Li et al (2013a, b) found a positive association between the c.-274C > G polymorphism and growth traits in Nanyang cattle suggesting that the presence of the G allelic variant could be responsible for a decreased gene promoter activity that, in turn, is responsible for the improved growth traits observed in CG and GG animals.…”
Section: Effects Of Polymorphism On Productive and Reproductive Traitsmentioning
confidence: 99%
See 3 more Smart Citations